Our newborn cases with brachial plexus palsy and its prognosis relation with clavicle fracture: A single-center retrospective study (Annals of Medical Research, 2021)
None
Keywords: Obstetric Complication; Brachial Plexus Palsy; Clavicular Fracture; Newborn.